Community genetics in the time of next‐generation molecular technologies. Issue 12 (13th June 2013) - Gugerli, Felix; Brandl, Roland; Castagneyrol, Bastien; Franc, Alain; Jactel, Hervé; Koelewijn, Hans‐Peter; Martin, Francis; Peter, Martina; Pritsch, Karin; Schröder, Hilke; Smulders, Marinus J. M.; Kremer, Antoine; et al.
<x xml:space="preserve">Abstract</x> Understanding the interactions of co‐occurring species within and across trophic levels provides key information needed for understanding the ecological and evolutionary processes that underlie biological diversity. As genetics has only recently been integrated into the study of community‐level interactions, the time is right for a critical evaluation of potential new, gene‐based approaches to studying communities. Next‐generation molecular techniques, used in parallel with field‐based observations and manipulative experiments across spatio‐temporal gradients, are key to expanding our understanding of community‐level processes. Here, we introduce a variety of '‐omics' tools, with recent studies of plant–insect herbivores and of ectomycorrhizal systems providing detailed examples of how next‐generation approaches can revolutionize our understanding of interspecific interactions. We suggest ways that novel technologies may convert community genetics from a field that relies on correlative inference to one that reveals causal mechanisms of genetic co‐variation and adaptations within communities.